Challenges on blue food provision - Morales-Nin, Beatriz; Zimmermann, Fabian; Merino, Gorka; Antelo, Luis T.; Murillas-Maza, Arantxa; Moksness, Erlend (Frontiers in Ocean Sustainability, 2024)
According to the objectives of Frontiers in Ocean Sustainability Section of Blue Food Provision, our aim is to contribute to the rising challenges created on marine resources due to global change, unsustainable practices, regulatory barriers and other constrains. We focus on existing and emerging knowledge, technologies and tools to build capacity and maximize the contribution of marine food systems (i.e. fisheries and aquaculture) to food security, nutrition and affordable healthy diets, and social equality, to ensure the achievement of the United Nations Sustainable Development Goals.